Reviewer Acknowledgements for Environmental Management and Sustainable Development, Vol. 11 No. 1 - Young, Jenny (Environmental Management and Sustainable Development, 2022)
Environmental Management and Sustainable Development (EMSD) would like to thank the following reviewers for reviewing manuscripts from November 1, 2021, to February 1, 2022. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Many authors, regardless of whether EMSD publishes their work, appreciate the helpful feedback provided by the reviewers. Macrothink Institute appreciates the following reviewers’ rigorous and conscientious efforts for this journal. Each of the reviewers listed below returned at least one review during this period. Christiane do Nascimento Monte, Universidade Federal Fluminense, Brazil Chuck Chuan Ng, Xiamen University Malaysia, Malaysia Dastun Gabriel Msuya, Sokoine University Of Agriculture, Tanzania Dilek Kaya-Akyüzlü, Ankara University, Turkey Giacomo Chiesa, Politecnico di Torino, Italy Hayssam Mohamed Ali, King Saud University, Egypt João Fernando Pereira Gomes, Instituto Superior de Engenharia de Lisboa, Portuguese Syakir Amir Ab. Rahman, International Islamic University Malaysia, Malaysia Taina da Silva Rocha Paz, Federal Fluminense University, Brazil